RETURN TO SPORT AFTER SURGICAL TREATED TIBIAL PLATEAU FRACTURES - Doul, Miloslav; Koehl, Philipp; Betsch, Marcel; Sesselmann, Stefan; Schuh, Alexander (Georgian medical news., 2023)
Introduction: Tibial plateau fractures (TPF) comprise 1% of all fractures, despite their limited frequency, due to their intraarticular nature they commonly result in significant functional morbidity. Generally, younger, and middle-aged men (64%) tend to have fractures as a result of high-energy trauma, such as high-speed motor vehicle accidents or falls from a considerable height, while older women have low-energy fractures (35%). While there is growing evidence on the clinical and radiological outcomes of surgical techniques, there remains limited evidence on return to sport following TPF. Aim of this retrospective study is to determine the sporting abilities of patients after operative treatment of TPF. Material and Method: 47 Patients (20 women, 27 men) who underwent surgical treatment for a TPF were surveyed by a questionnaire to determine their sporting activity were followed-up a mean of 47.6 months (Min: 12, Max: 115). All the patients fractures were systematically assessed using AO-Classification. The Lysholm-Gillquist scores, IKDC Score, Injury-Psychological Readiness to Return to Sport (I-PRRS) scales and ACL-Return to Sport Injury Scale (ACL-RSI) were used to assess clinical outcomes. Results: All fractures united, and no revision surgeries were required. There were no intraoperative complications. Mean postoperative IKDC score was 75 (Min:13, Max: 100), mean postoperative Lysholm score was 82 (Min: 5, Max: 100), mean ACL-Return to Sport Injury Scale (ACL-RSI) was 66 (Min: 0, Max: 100), Injury-Psychological Readiness to Return to Sport Scale (I-PRRS-Scale) was 39 (Min: 0, Max: 80). 31/47 patients were able to return to their former-sports-activity level, 8/47 did not achieve their former sports activity level before injury, 2/47 cases changed their kind of sport and 6/47 stopped sporting activities. Conclusion: Tibial plateau fractures-a severe injury-have a great effect on patients in terms of quality and quantity of sporting activity. Nevertheless, most of our surgical treated patients were satisfied with the outcome with good values in the Lysholm-score, I-PRRS-Scale, IKDC score and ACL-Return to Sport Injury Scale.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Fracture; Physical activity; Return to sports; Surgery; Tibial plateau